Extraction and Characterization of Pectin from Grape Fruit (Citrus paradisi) and Valencia (Citrus sinensis) - الحاج رهف; الدياب ديمة (Latakia University Journal -Medical Sciences Series, 2022)
Pectin is a polysaccharide naturally present in most plant tissues, its name comes from the Greek word "Pektos", which means tough and hard, indicating the ability of pectin to form hydrogels. the characteristics of pectin are mainly related to its microstructure, pectin has gained increasing importance over the years due to those characteristics. The study includes two types of Citruses (Valencia-Grapefruit), The samples were collected during two different periods, including the beginning and end of the citrus season in Syria, in order to study the effect of the maturity stage on the yield of pectin extraction, in addition to its effect on the Degree of Esterification (DE) and Equivalent Weight (EW). This study aimed to extract pectin using the traditional way of extraction (Thermal Extraction) from two types of citruses and the Determination of some of its qualitative properties (Color and Solubility of extracted pectin) and quantitative properties (Extraction yield, Degree of Esterification, Equivalent Weight, Moisture, and Ash). It was found that the color of the pectin differs according to the source of extraction, and that some of the quantitative properties of the extracted pectin were significantly affected by the time of citrus harvesting.